The values and principles underpinning community engagement approaches to tackling antimicrobial resistance (AMR). (13th December 2019) - Mitchell, Jessica; Cooke, Paul; Baral, Sushil; Bull, Naomi; Stones, Catherine; Tsekleves, Emmanuel; Verdezoto, Nervo; Arjyal, Abriti; Giri, Romi; Shrestha, Ashim; King, Rebecca
ABSTRACT: This paper presents seven values underpinning the application of Community Engagement (CE) approaches to the One Health challenge of antimicrobial resistance (AMR) developed during an international workshop in June 2019. We define a value as a quality or standard which a CE project is aiming for, whilst a principle is an objective which underpins the value and facilitates its achievement. The values of Clarity, Creativity, (being) Evidence-led, Equity, Interdisciplinarity, Sustainability and Flexibility were identified by a network of 40 researchers and practitioners who utilise CE approaches to tackle complex One Health challenges including, but not limited to, AMR. We present our understanding of these seven values and their underlying principles as a flexible tool designed to support stakeholders within CE for AMR projects. We include practical guidance on working toward each value, plus case studies of the values in action within existing AMR interventions. Finally, we consider the extent to which CE approaches are appropriate to tackle AMR challenges. We reflect on these in relation to the tool, and current literature for both CE and AMR research. Authors and co-producers anticipate this tool being used to scene-set, road map and trouble shoot the development, implementation, and evaluation of CE projects to address AMR and other One Health challenges. However, the tool is not prescriptive but responsive to the context and needs of the community, opening opportunity to build a truly collaborative and community-centred approach to AMR research.